Effect of weld parameters on the mechanical properties of friction-stir-welded heat-treatable AA6061-T6 - Tra, Tran Hung (Vietnam Journal of Science and Technology, 2019)
Effect of welding parameters on the mechanical properties of the friction stir welding of heat-treatable 6061-T6 was experimentally investigated. The influence of the welding rates on the hardness, tensile strength, bending strength, and the impact energy of the welding were investigated. The experimental results showed the joint could be obtained with free defects. However, both the tensile and bending strength of the joint were quite low compared to that of the base alloy 6061. The bending ductility of the joints were improved significantly. While the impact resistance at around the welded zone was higher than that of the base alloy, the impact resistance at the weld center was remarkable low.